Rapid movement and transcriptional re‐localization of human cohesin on DNA. (31st October 2016) - Davidson, Iain F; Goetz, Daniela; Zaczek, Maciej P; Molodtsov, Maxim I; Huis in 't Veld, Pim J; Weissmann, Florian; Litos, Gabriele; Cisneros, David A; Ocampo‐Hafalla, Maria; Ladurner, Rene; Uhlmann, Frank; Vaziri, Alipasha; et al.
Abstract: The spatial organization, correct expression, repair, and segregation of eukaryotic genomes depend on cohesin, ring‐shaped protein complexes that are thought to function by entrapping DNA. It has been proposed that cohesin is recruited to specific genomic locations from distal loading sites by an unknown mechanism, which depends on transcription, and it has been speculated that cohesin movements along DNA could create three‐dimensional genomic organization by loop extrusion. However, whether cohesin can translocate along DNA is unknown. Here, we used single‐molecule imaging to show that cohesin can diffuse rapidly on DNA in a manner consistent with topological entrapment and can pass over some DNA‐bound proteins and nucleosomes but is constrained in its movement by transcription and DNA‐bound CCCTC‐binding factor (CTCF). These results indicate that cohesin can be positioned in the genome by moving along DNA, that transcription can provide directionality to these movements, that CTCF functions as a boundary element for moving cohesin, and they are consistent with the hypothesis that cohesin spatially organizes the genome via loop extrusion. Synopsis: Human cohesin rings entrap DNA and rapidly translocate along DNA by diffusion. Cohesin can pass over small DNA‐bound proteins but is constrained in its movement by transcription and DNA‐bound CCCTC‐binding factor (CTCF). Single‐molecule imaging of cohesin bound to immobilized DNA reveals that cohesin binds to DNA in a salt‐resistant manner and translocates with a diffusion coefficient higher than many other DNA‐binding proteins (1.72 ± 0.1 µm 2 /s). Cohesin is released from DNA following cleavage of DNA or the cohesin ring, consistent with topological entrapment. Cohesin can diffuse past obstacles with a diameter < ˜11 nm, including nucleosomes, but not those with a diameter > ˜21 nm, such as QDots. CTCF constrains the movement of cohesin. Transcribing T7 RNA polymerase provides directionality to cohesin. Abstract : Human cohesin rings entrap DNA and rapidly translocate along DNA by diffusion. Cohesin can pass over small DNA‐bound proteins but is constrained in its movement by transcription and DNA‐bound CCCTC‐binding factor (CTCF).